2016
DOI: 10.1155/2016/3892685
|View full text |Cite
|
Sign up to set email alerts
|

Effect of miR-146a/bFGF/PEG-PEI Nanoparticles on Inflammation Response and Tissue Regeneration of Human Dental Pulp Cells

Abstract: Introduction. Inflammation in dental pulp cells (DPCs) initiated by Lipopolysaccharide (LPS) results in dental pulp necrosis. So far, whether there is a common system regulating inflammation response and tissue regeneration remains unknown. miR-146a is closely related to inflammation. Basic fibroblast growth factor (bFGF) is an important regulator for differentiation. Methods. To explore the effect of miR-146a/bFGF on inflammation and tissue regeneration, polyethylene glycol-polyethyleneimine (PEG-PEI) was syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…MicroRNAs (miRNAs or miRs) are a type of non-coding, small RNA molecule made up of 18-22 nucleotides, which regulate the expression of proteins at mRNA level in eukaryotes (11)(12)(13). The pathogenesis of pulpitis is accompanied by changes in the expression of a variety of miRNA molecules and proteins, suggesting that miRNA may serve important roles in the regulation of proteins associated with the disease (14)(15)(16). In the present study, the expression of IL-6R mRNA and protein were examined in pulp tissues, blood and saliva from patients with pulpitis.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs or miRs) are a type of non-coding, small RNA molecule made up of 18-22 nucleotides, which regulate the expression of proteins at mRNA level in eukaryotes (11)(12)(13). The pathogenesis of pulpitis is accompanied by changes in the expression of a variety of miRNA molecules and proteins, suggesting that miRNA may serve important roles in the regulation of proteins associated with the disease (14)(15)(16). In the present study, the expression of IL-6R mRNA and protein were examined in pulp tissues, blood and saliva from patients with pulpitis.…”
Section: Introductionmentioning
confidence: 99%
“…In pheochromocytoma PC12 cells, BPS can regulate the expression of miR-10b to inhibit the expression of KLF4 and induce cell migration (Jia et al, 2018). It has been reported that miR-15a (Zhu et al, 2017), miR-146a (Liu et al, 2016), and miR-195 (Wang et al, 2017) can also regulate the mRNA stability and expression of bFGF.…”
Section: Discussionmentioning
confidence: 99%
“…[60] Polyethyleneimine (PEI) derivatives have also been extensively studied as miRNA delivery systems, [19,61,62] and specifically PEI-poly(ethylene glycol) (PEG) nanoparticles (NP) have recently demonstrated interesting profiles when encapsulated within poly(lactic-co-glycolic acid) (PLGA) microspheres in a poly(l-lactic acid) (PLLA) scaffold [63] or as part of a calcium chloride cross-linked alginate hydrogel system. [64] PEI is watersoluble and easily attracts negatively charged ions to aid the polyplex cargo escape the endolysosomal compartment in what is known as "the proton sponge effect." [65] The extent of this effect is dependent on a parameter termed N/P ratio, that is, the proportion of moles of nitrogen in PEI to moles of phosphate in the cargo.…”
Section: Nonviral Vectorsmentioning
confidence: 99%